Leadership and Its Position in Islamic Education - Erick Yusuf; Abas Mansur Tamam; Adian Husaini (International Journal of Nusantara Islam, 2021)
This study aims to describe leadership and its position in Islamic education. The method used in this research is a literature study by collecting (material materials) sourced from various books, journals, and other sources. The results of the study indicate that an effective leader in an educational institution is able to motivate his staff (teachers and non-teachers) to excel and work with high spirits. He will also be able to build good relationships with parents and the surrounding community for the betterment of the institution he leads. Achievement motivation and high work spirit of school/madrasah staff will give birth to better quality education services which then produce students who excel.